2004
DOI: 10.1111/j.1365-2966.2004.07675.x
|View full text |Cite
|
Sign up to set email alerts
|

The stellar velocity distribution in the solar neighbourhood

Abstract: We explore the heating of the velocity distribution in the solar neighbourhood by stochastic spiral waves. Our investigation is based on direct numerical integration of initially circular test-particle orbits in the sheared sheet. We confirm the conclusion of other investigators that heating by spiral structure can explain the principal features of the age-velocity dispersion relation and other parameters of the velocity distribution in the solar neighbourhood. In addition, we find that heating by strong trans… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
153
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 173 publications
(162 citation statements)
references
References 45 publications
9
153
0
Order By: Relevance
“…Sellwood (2010Sellwood ( , 2011 explored the hypothesis of recurrent short-lived spiral transients. De Simone et al (2004) already showed that the observational features could be reproduced from a succession of strong spiral transients.…”
Section: Introductionmentioning
confidence: 99%
“…Sellwood (2010Sellwood ( , 2011 explored the hypothesis of recurrent short-lived spiral transients. De Simone et al (2004) already showed that the observational features could be reproduced from a succession of strong spiral transients.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies of heating mechanisms have concentrated on heating from transient spiral density waves (e.g., Carlberg et al 1985;De Simone et al 2004;Jenkins 1992). However in that case changes in the stellar velocity dispersion only occur during the spirals' growth and decay.…”
Section: Stochastic Heating From Multiple Spiral Wavesmentioning
confidence: 99%
“…The timescale between when a star is free from any residual gas from its stellar nursery and when it is kinematically thermalised due to disk-heating mechanisms is similar (De Simone et al 2004). This may indicate that disk-heating has a direct effect on stellar magnetic fields.…”
Section: Residual Molecular Gasmentioning
confidence: 99%